Trade Barriers and Economic Health: Insights from International Economics - Imran Tajuddin (Amkop Management Accounting Review (AMAR), 2023)
This research investigates the interplay between trade barriers and economic health within international economics, aiming to provide valuable insights for policymakers and stakeholders. The study aims to uncover the nuanced impacts of tariffs, quotas, and non-tariff barriers (NTBs) on economic indicators such as GDP growth, employment rates, and income distribution across diverse national contexts and economic sectors. The research design adopts a mixed-methods approach, integrating quantitative analysis and qualitative exploration. Quantitative analysis reveals the differential effects of trade barriers on economic indicators, emphasizing the complexities in policy formulation. Qualitative insights from stakeholder interviews and case studies enrich the understanding of underlying mechanisms driving these effects, highlighting the importance of evidence-based policymaking. The findings underscore the multifaceted nature of trade barriers' impact on economic health, emphasizing the necessity of balanced policy strategies. The discussion delves into the implications of poorly managed trade barriers on economic growth and income distribution, advocating for evidence-based policy formulation to foster sustainable economic development. The implications extend to practical applications, guiding policymakers in crafting effective policies while providing actionable insights for practitioners and avenues for further research refinement.